ADIKSI GAME ONLINE DENGAN PENDEKATAN TEKNIK BEHAVIOURAL CONTRACT (Studi Kasus terhadap Peran Guru BK SMKN 2 LUWU UTARA) - Sheila Nur Khaeromah; Muhammad Irham Zainuri; Arman Bin Anuar (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Online game addiction among students has become an increasingly significant problem as it negatively affects learning concentration, discipline, and academic responsibility. This study aims to describe the implementation of the behavioural contract technique in guidance and counseling services to address online game addiction. This research employed a qualitative approach with a case study design conducted at SMKN 2 Luwu Utara, involving one school counselor and three students identified as experiencing online game addiction. Data were collected through in-depth interviews and non-participant observation. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings indicate that addictive behavior is influenced by internal factors such as boredom and low self-control, as well as external factors including peer influence and easy access to digital devices. The implementation of the behavioural contract was conducted through behavioral agreements, clear goal setting, reinforcement, and continuous monitoring. This intervention showed positive behavioral changes, indicated by reduced gaming intensity and improved learning discipline. The findings imply that the behavioural contract technique is effective for school counselors as an intervention strategy to reduce online game addiction among students. This technique can promote positive behavioral changes and enhance students’ self-control and responsibility, making it applicable in school guidance and counseling services.